SOSOK PEREMPUAN INDONESIA DALAM NOVEL-NOVEL INDONESIA MODERN - Djoko Sarryono (LITERA, 2009)
This study aims to describe female Indonesian figures constructed in modern Indonesian novels. The data sources were Indonesian novels presenting female main characters. The data were analyzed by means of a cyclical interactive analysis involving hermeneutic reading and understanding, holistic classification accordingto the research focus, and hermeneutic reinterpretation. The findings are as follows. There are a variety of female Indonesian figures represented in several serious Indonesian novels. Female figures’ physical-biological identity, ethnic identity, socio-economic identity, cultural orientation, worldview, life view, life attitude, andlifestyle are relatively varied. Basically, however, female figures from the modern upper-middle class are much more dominant and stronger than those from the traditional lower class. Therefore, serious modern Indonesian novels seem to an arena of ideological introduction and operation for the interest of Indonesian middle and upper-middle classes.